PENATAAN HUKUM MENUJU HUKUM IDEAL DALAM PENGATURAN PEMILUKADA - Wendy Melfa (Masalah-Masalah Hukum, 2013)
Abstract The election of Head of region as the democracy mechanism to the head of region that the application is based on the Law Number 23 2004 about Regional Government is still found some problems, such as the application of the head of region election gives the burden the government finance plan so that it’s not really efficient and effective, and also the head of region election results the unharmonious head and the vice head of the region (about 93.84% all over Indonesia). So that for the consequence as the lawful country, Indonesia has to revise that problem that needs to administer the law to become the ideal law in regulating the head of region election. The ideal law regulation will become the basic to the application of the head of region election with the better result as the effort to accomplish the purpose of autonomy region in boosting the society welfare of the autonomy region’s people as the implementation of people’s sovereignty through the process of political decentralization to the autonomy region. Keywords: Ideal Law, People’s welfare, People’s Sovereignty.   Abstrak Pemilukada sebagai suatu mekanisme demokrasi untuk pengisian jabatan kepala daerah yang penyelenggaraannya didasari Undang-Undang Nomor 32 Tahun 2004 tentang Pemerintahan Daerah dalam penerapannya masih dijumpai berbagai persoalan, diantaranya; pelaksanaan pemilukada cukup membebani anggaran pemerintah sehingga dirasa tidak efisen dan efektif, juga pemilukada justru menghasilkan pasangan kepala daerah yang tidak harmonis (93,84 % se Indonesia). Oleh karena itu sebagai konsekuensi Indonesia negara hukum, maka untuk memperbaiki berbagai persoalan tersebut, perlu dilakukan penataan hukum menuju hukum ideal dalam pengaturan pemilukada. Pengaturan hukum ideal akan menjadi dasar untuk penyelenggaraan pemilukada dengan hasil yang lebih baik sebagai upaya untuk mewujudkan tujuan otonomi daerah dalam meningkatkan kesejahteraan masyarakat daerah otonom sekaligus perwujudan kedaulatan rakyat melalui proses desentralisasi politik kepada daerah otonom. Kata kunci: Hukum ideal, Kesejahteraan rakyat, kedaulatan rakyat.